Generating Programming Puzzles to Train Language Models - Haluptzok, Patrick; Bowers, Matthew; Kalai, Adam Tauman (Workshop, 2022)
This work shows how one can use large-scale Language Models (LMs) to automatically generate programming problems with verified solutions, in the form of “programming puzzles,” which can then in turn be used to fine-tune other LMs to solve more difficult programming puzzles. This work builds on two recent developments. First, LMs have achieved breakthroughs in non-trivial reasoning and algorithm implementation, generating code that can solve some intermediate level competitive programming problems. However, training code LMs involves curated sets of natural-language problem descriptions and source-code tests and solutions, which are limited in size. Second, a new format of programming challenge called a programming puzzle was introduced, which does not require a natural-language description and is directly specified by a source-code test. In this work we show how generating synthetic programming puzzles and solutions, verified for correctness by a Python interpreter, can be used to improve performance in solving test puzzles from P3, a public benchmark set of Python Programming Puzzles. In particular, we find that knowledge is distilled both from the interpreter and the language model that generates and solves the synthetic puzzles. It also opens the door to iterative self-improvement for LMs in future work.